Beyond biomedical care: the role of psychosocial support in improving birth outcomes in rural Uttar Pradesh - Shukla, Archana; Purohit, Neetu (International Journal Of Community Medicine And Public Health, 2026)
Background: Maternal health encompasses multiple dimensions, including nutritional status, antenatal care (ANC), and psychosocial well-being, all of which significantly influence pregnancy outcomes. While ANC coverage has improved however, Neonatal mortality remains a major concern. Prematurity and low birth weight account for 35% of neonatal deaths, hence it is pertinent to explore the reasons beyond medical care. Methods: This observational case–control study was conducted in Raebareli district, Uttar Pradesh. A total of 425 women were enrolled, including 212 cases who delivered low birth weight (<2500 g) babies and control group comprised 213 women without LBWs babies. Results: In the bivariate analysis, a highly significant association was observed between the number of ANC check-ups received and adverse birth outcomes such as low birth weight and preterm birth (χ²=162.50, p=4.26 × 10⁻³⁴). Even after excluding women had four or more ANC visits, the psychosocial factors continued to show strong associations with adverse pregnancy outcomes. Women who reported low family support had 3.41 times higher odds of delivering a low-birth-weight or preterm newborn (OR=3.41, 95% CI: 1.91–6.12). Similarly, partner support emerged as another significant psychosocial determinant (OR=2.86, 95% CI: 1.57–5.23; p=0.0006). Conclusions: This study demonstrates that psychosocial factors play an independent and equally critical role in determining birth outcomes.